Peran Media Sosial dalam Mengedukasi Masyarakat Tentang Zakat: Studi Kasus Basnaz SUMUT - Azrai Harahap; Hasan Sazali (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate the role of social media in educating and disseminating information to the public about zakat, by taking the North Sumatra National Zakat Amil Agency (BASNAZ) case study. As the institution responsible for collecting and distributing zakat in the region, BASNAZ has an important role in increasing public awareness and understanding of zakat. Social media has become an important communication channel for BASNAZ to reach a wider audience and strengthen community participation in zakat activities. This research method involves a qualitative approach, by collecting data through interviews with North Sumatra BASNAZ management, observation of their social media content, and analysis of related documents. The data was then analyzed thematically to identify the strategies and best practices used by BASNAZ in using social media for educational purposes about zakat. The research results show that social media has become an effective instrument for BASNAZ North Sumatra in educating the public about zakat. Through platforms such as Facebook, Instagram and Twitter, BASNAZ can convey relevant information about zakat obligations, lessons learned, as well as how to manage and distribute zakat in a way that is easy for the public to understand. In addition, the two-way interaction between BASNAZ and social media users allows for a deeper dialogue on zakat-related issues. However, challenges also arise, including problems with the authenticity of information, limited accessibility for people who do not have internet access, and competition with other content on social media. Therefore, this research also identifies several recommendations to increase the effectiveness of the use of social media in educating the public about zakat, including increasing collaboration with local influencers, developing engaging content, and increasing the use of text-based platforms to reach underserved communities online. The findings of this research have practical implications for BASNAZ and similar organizations in improving their communication strategies through social media, as well as for researchers and practitioners in the fields of marketing communications and zakat education. Apart from that, this research also contributes to the understanding of the role of social media in supporting philanthropic and charitable activities in the digital era.